A study on water supply system in rural at FELDA and FELCRA's settlements / Muhammad Akram Ismail - Ismail, Muhammad Akram (2012)
Water is the most important thing in our lives. Water need to be manage properly and threat well before can distribute to consumer. Each state got their own division and department where this people are responsible on supplying water, water quality, water management and treatments, and also Non-revenue water. All of this is needed in order to achieve acceptable standard. In this research is about to study on water supply system, source of water, how they treat and manage water and who responsible for all the process- and lastly to supply clean and safe water to each houses to fulfill consumer need. Finally is to give opinion and advice to respondent and related person on how to avoid water interruption from happen and at mean time how to solve water problem in case of water interruption.